New and developing non-adrenoreceptor small molecule drugs for the treatment of asthma. (11th February 2017) - Thomson, Neil C
ABSTRACT: Introduction: Inhaled corticosteroids (ICS) alone or in combination with an inhaled long-acting beta2 -agonist (LABA) are the preferred long-term treatment for adults and adolescents with symptomatic asthma. Additional drugs include leukotriene-receptor antagonists, slow-release theophylline and the long-acting muscarinic antagonist (LAMA) tiotropium (approved in 2015). There is a need for more effective therapies, as many patients continue to have poorly controlled asthma. Areas covered: New and developing long-acting non-adrenoreceptor synthetic drugs for the treatment of symptomatic chronic asthma despite treatment with an ICS alone or combined with a LABA. Data was reviewed from studies published up until November 2016. Expert opinion: Tiotropium improves lung function and has a modest effect in reducing exacerbations when added to ICS alone or ICS and LABA. The LAMAs umeclidinium and glycopyrronium are under development in fixed dose combination with ICS and LABA. Novel small molecule drugs, such as CRTH2 receptor antagonists, PDE4 inhibitors, protein kinase inhibitors and nonsteroidal glucocorticoid receptor agonists and 'off-label' use of licensed drugs, such as macrolides and statins are under investigation for asthma, although their effectiveness in clinical practice is not established. To better achieve the goal of developing effective novel small molecule drugs for asthma will require greater understanding of mechanisms of disease and the different phenotypes and endotypes of asthma.